2000
DOI: 10.1096/fasebj.14.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate modulation of Sp1, NF‐kappa B, and p53 in confluent human malignant melanoma cells after ionizing radiation

Abstract: Regulation of transcriptional responses in growth-arrested human cells under conditions that promote potentially lethal damage repair after ionizing radiation (IR) is poorly understood. Sp1/retinoblastoma control protein (RCP) DNA binding increased within 30 min and peaked at 2-4 h after IR (450-600 cGy) in confluent radioresistant human malignant melanoma (U1-Mel) cells. Increased phosphorylation of Sp1 directly corresponded to Sp1/RCP binding and immediate-early gene induction, whereas pRb remained hypophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 47 publications
(70 reference statements)
3
42
0
Order By: Relevance
“…Transcription factors belonging to the Sp family are known to bind to GC-rich boxes. The family member Sp1 has been shown to mediate oxidative stress-induced gene transcription (38)(39)(40). Thus, we decided to look at whether Sp1 may represent the transcription factor that activates the caveolin-1 gene after oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors belonging to the Sp family are known to bind to GC-rich boxes. The family member Sp1 has been shown to mediate oxidative stress-induced gene transcription (38)(39)(40). Thus, we decided to look at whether Sp1 may represent the transcription factor that activates the caveolin-1 gene after oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of NF-kB mediates the synthesis of inflammatory cytokines (Zhou et al, 2001) and the modulation of radiosensitivity. Several studies suggested that NF-kB promoted radiosensitivity (Yang et al, 2000); however, accumulating evidences demonstrated that radiosensitization can be achieved by inhibiting NF-kB activation in many cancer cell types (Yamagishi et al, 1997;Eichholtz-Wirth and Sagan, 2000;Kato et al, 2000;Didelot et al, 2001;Russo et al, 2001). Consistent with these observations, the inhibition of radiation-mediated NF-kB activation directly suppressed MMP-9 synthesis and activity, which contributes to arsenic-inhibited tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment of human malignant melanoma cells with ionizing radiation induces the coordinated activation of NF-κB and other regulators of transcription 24 . The activation of NF-κB correlates with CXCL8 expression, growth, angiogenesis and metastasis of human melanoma cells 25,26 .…”
Section: Cxcl8 Anoxia and Tumour Aggressivenessmentioning
confidence: 99%